Synthesis and Biological Evaluation of O-6-Aminoalkyl-Hispidol Analogs as Multifunctional Monoamine Oxidase-B Inhibitors towards Management of Neurodegenerative Diseases - Hassan, Ahmed H. E.; Kim, Hyeon Jeong; Park, Keontae; Choi, Yeonwoo; Moon, Suyeon; Lee, Chae Hyeon; Kim, Yeon Ju; Cho, Soo Bin; Gee, Min Sung; Lee, Danbi; Park, Jong-Hyun; Lee, Jong Kil; et al. (MDPI AG, 2023)
Oxidative catabolism of monoamine neurotransmitters by monoamine oxidases (MAOs) produces reactive oxygen species (ROS), which contributes to neuronal cells' death and also lowers monoamine neurotransmitter levels. In addition, acetylcholinesterase activity and neuroinflammation are involved in neurodegenerative diseases. Herein, we aim to achieve a multifunctional agent that inhibits the oxidative catabolism of monoamine neurotransmitters and, hence, the detrimental production of ROS while enhancing neurotransmitter levels. Such a multifunctional agent might also inhibit acetylcholinesterase and neuroinflammation. To meet this end goal, a series of aminoalkyl derivatives of analogs of the natural product hispidol were designed, synthesized, and evaluated against both monoamine oxidase-A (MAO-A) and monoamine oxidase-B (MAO-B). Promising MAO inhibitors were further checked for the inhibition of acetylcholinesterase and neuroinflammation. Among them, compounds 3aa and 3bc were identified as potential multifunctional molecules eliciting submicromolar selective MAO-B inhibition, low-micromolar AChE inhibition, and the inhibition of microglial PGE(2) production. An evaluation of their effects on memory and cognitive impairments using a passive avoidance test confirmed the in vivo activity of compound 3bc, which showed comparable activity to donepezil. In silico molecular docking provided insights into the MAO and acetylcholinesterase inhibitory activities of compounds 3aa and 3bc. These findings suggest compound 3bc as a potential lead for the further development of agents against neurodegenerative diseases.